Instytucjonalne formy wspierania przedsiębiorczości - Zeman-Miszewska, Ewa (Institutional Forms of Supporting the Entrepreneurship, 2006)
Entrepreneurship can be see both as an autonomous and supporting activity. As a supportive activity it can appear both as a role of big companies and as a role of profiled organisations. Generally, the Polish system of supporting is quite similar to the other systems within the European Union. However, the main concern is the quality standards of the support paid to the small and medium size firms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 687-691